Pediatric faculty and residents’ perspectives on In-Training Evaluation Reports (ITERs) - Patel, Rikin; Drover, Anne; Chafe, Roger (Canadian Medical Education Journal, 2015)
Background: In-training evaluation reports (ITERs) are used by over 90% of postgraduate medical training programs in Canada for resident assessment. Our study examined the perspectives of faculty and residents in one pediatric program as a means to improve the ITER as an evaluation tool. Method: Two separate focus groups were conducted, one with eight pediatric residents and one with nine clinical faculty within the pediatrics program of Memorial University’s Faculty of Medicine to discuss their perceptions of, and suggestions for improving, the use of ITERs. Results: Residents and faculty shared many similar suggestions for improving the ITER as an evaluation tool. Both the faculty and residents emphasized the importance of written feedback, contextualizing the evaluation and timely follow-up. The biggest challenge appears to be the discrepancy in the quality of feedback sought by the residents and the faculty members’ ability to do so in a time effective manner. Others concerns related to the need for better engagement in setting rotation objectives and more direct observation by the faculty member completing the ITER. Conclusions: The ITER is a useful tool in resident evaluations, but a number of issues relating to its actual use could improve the quality of feedback which residents receive.